Nonpositive solutions to a certain functional differential inequality - Lomtatidze, A.; Opluštil, Z.; Šremr, J. (Нелінійні коливання, 2009)
In the paper, efficient conditions are found guaranteeing that every solution to the problem
u'(t) ≥ ι(u)(t), u(a) ≥ h(u)
is nonpositive, where ι : C([a, b]; R) → L([a, b]; R) and h : C([a, b]; R) → R are linear bounded operators. The results obtained are very useful for the investigation of the question on solvability and unique
solvability of the nonlocal boundary-value problems for the first order functional differential equations in
both linear and nonlinear cases. Знайдено ефективнi умови для того, щоб кожен розв’язок задачi
u'(t) ≥ ι(u)(t), u(a) ≥ h(u),
де ι : C([a, b]; R) → L([a, b]; R) h : C([a, b]; R) → R — лiнiйнi обмеженi оператори, був недодатним. Отриманi результати є корисними для вивчення задачi розв’язностi та iснування єдиного
розв’язку нелокальних граничних задач для функцiонально-диференцiальних рiвнянь першого
порядку як в лiнiйному, так i в нелiнiйному випадках.